2021
DOI: 10.1111/ahg.12441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high variation in transcript expression on identifying differentially expressed genes in RNA‐seq analysis

Abstract: Summary Great efforts have been made on the algorithms that deal with RNA‐seq data to enhance the accuracy and efficiency of differential expression (DE) analysis. However, no consensus has been reached on the proper threshold values of fold change and adjusted p‐value for filtering differentially expressed genes (DEGs). It is generally believed that the more stringent the filtering threshold, the more reliable the result of a DE analysis. Nevertheless, by analyzing the impact of both adjusted p‐value and fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Similarly, e dgeR analysis revealed that COL11A2 was significantly down-regulated in T2, T3, and T4 stages, but the difference was not significant in Wilcoxon tests. By examining the read count values of COL2A1 and COL11A2, the large fold change values obtained using edgeR were caused by a few extreme outlier expression values, which was consistent with previous studies 23 , 24 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, e dgeR analysis revealed that COL11A2 was significantly down-regulated in T2, T3, and T4 stages, but the difference was not significant in Wilcoxon tests. By examining the read count values of COL2A1 and COL11A2, the large fold change values obtained using edgeR were caused by a few extreme outlier expression values, which was consistent with previous studies 23 , 24 .…”
Section: Resultssupporting
confidence: 89%
“…As a landmark cancer genomics program, TCGA sequenced and molecularly characterized a great many cases of various kinds of primary cancer samples. Due to the high variation in mRNA expression, differentially expressed genes (DEGs) identified using a larger sample size are more reliable in RNA-Seq analysis 23 , 24 . The number of GC samples in TCGA is much larger than that in any single study in other databases, and RNA-Seq is more accurate than the microarray technology; however, the expression patterns of collagen family genes in GC samples in TCGA has not been systematically explored.…”
Section: Introductionmentioning
confidence: 99%
“… 60 ; according to a study in ref. 61 , studies with smaller sample sizes had greater variation in the number of transcripts quantified for each gene.…”
Section: Resultsmentioning
confidence: 99%
“…Inter-tumoral and intra-tumoral heterogeneity is recognized in many solid tumors, creating obstacles in the identification and development of new biomarkers (28,29). A recent paper by Childs et al demonstrated significant intra-and inter patient genomic heterogeneity in circulating tumor cells (CTC) from NETs (29).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor micro-environment is a complex ecosystem in which cancer cells interact with a diverse range of immune, stromal and endothelial cells, constantly shaping and changing the molecular biology of a tumor ( 27 ). Inter-tumoral and intra-tumoral heterogeneity is recognized in many solid tumors, creating obstacles in the identification and development of new biomarkers ( 28 , 29 ). A recent paper by Childs and coworkers demonstrated significant intra- and inter-patient genomic heterogeneity in circulating tumor cells from NETs ( 29 ).…”
Section: Discussionmentioning
confidence: 99%